Alipay entered Malaysia: a closer look at the new market entry strategy driven by Chinese tourists. (15th July 2020) - Chew, Boon Cheong; Shen, Xiaobai; Ansell, Jake
Abstract : Purpose: This study aims to investigate the entrance of Chinese-based Alipay's mobile-payment (m-payment) technology into Malaysia. Malaysia allowed this entry of the first foreign m-payment company because it would allow Chinese tourists spending while they are visiting Malaysia. It will view this entrance from a Malaysian perspective. Design/methodology/approach: The views of Malaysian players (Bank Negara Malaysia officers, three Malaysian banks' officers, Alipay-Malaysia officers, airport section manager, convenience store manager and airport store sales executive) were sought via qualitative interview concerning Alipay's entry into the Malaysian market. Respondents who had relevant knowledge and/or were involved in Alipay m-payment technology development in Malaysia were contacted, while there remainder were obtained by snowballing. Secondary data was collected from Bank Negara Malaysia's policy, three Malaysian banks' reports, the Alipay-Malaysia public statements and the Airport and Convenience Store reports. Triangulation using primary and secondary data was used to safeguard the validity and reliability of the outcomes. Findings: The entry strategy used by Alipay was different from those reported in previous studies. The establishment of Alipay-Malaysia was the first element of the "mode of entry" gaining pioneer status in Malaysia. The next stage was gaining support from Bank Negara Malaysia-Malaysian Central Bank and three Malaysian banks (Maybank, Public Bank and CIMB) through collaborative ventures with Alipay-Malaysia Sdn. Bhd., leading to acceptance nationwide by local merchants. The key driver of acceptance being Chinese outbound tourists in Malaysia. Research limitations/implications: This case study was conducted during the early implementation of Alipay in Malaysia from 2015 until April 2019. During this period, there were challenges due to the lack of primary data. These were overcome by the support from the respondents and the secondary data. Practical implications: This study contributes to insights from a different entry strategy that used tourism as a leading force. This can give guidance to other m-payment service providers or other countries as m-payment technology recipient about "market entry strategy" and "modes of entry" following Alipay's approach. Originality/value: To date, no study has been conducted to investigate the nature of Alipay m-payment in Malaysia. This qualitative study has examined the new phenomenon regarding how Alipay entered the Malaysian market. Moreover, this study can also contribute new insights into the existing theory of "market entry strategy" in terms of Alipay's tourist-based approach.